Bioeconomy development and using of intellectual capital for the creation of competitive advantages by SMEs in the field of biotechnology - Daniel Adrian Gârdan; Mihai Andronie; Iuliana Petronela Gârdan; Irina Elena Andronie; Mariana Iatagan; Iulian Hurloiu (Amfiteatru Economic Journal, 2018)
The article aims to present a thorough research on the perceptions and opinions of the Romanian managers of small and medium enterprises in applied biotechnology on the importance of intellectual capital and the application of knowledge management principles to create and maintain competitive advantages. At the basis of the development of bio-economics, there is a successful implementation not only of top biotechnologies but also of new economic models that engage the economic agents in complex exchanges. Biotechnology companies are a true "engine" that helps the development of bio-economy basic mechanisms, optimization of their work having long-term repercussions. Companies that develop a sustainable knowledge management system that they integrate into their marketing strategy have the most prominent position on the market and gain multiple competitive advantages. The research, based on the qualitative research methodology in the form of an in-depth interview, highlights that the strategic decision regarding the implementation of a knowledge management system and the intelligent use of intellectual capital resources are correlated with variables such as: the managers' level of education in the field, corelating managers' activity to organizational culture. Knowledge, for new business models, is a good asset that can be capitalized; from this perspective, the implications at the level of marketing strategies are in the same time diverse and complex. Biotechnology SMEs will adapt to requirements by developing competitive advantages as a result of establishing relationships and developing exchanges within strategic alliances and less according to a classical model based on attributes that aims positioning of products or services above those of the competition.
Keywords: M31; 330; intellectual capital; bioeconomy; knowledge management; biotechnology; competitive advantage